Development of a method for optimal location of emergency water reservoirs for FFE suppression using AHP and GIS - Tanoumand, Ali; Mashayekhi, Mohammadreza; S. Ramadan, Mona; Majdi, Ali (Frontiers in Built Environment, 2025)
IntroductionIdentifying optimal locations for constructing emergency water reservoirs for Fire Following Earthquake (FFE) suppression is recognized as a key factor in reducing financial and human losses within FFE crisis management strategies; however, previous studies have not provided a comprehensive model for this purpose.MethodsThis study proposes a method that integrates potential post-earthquake damages, accessibility conditions, and economic considerations to identify the most suitable initial locations for these reservoirs. Based on operational needs in post-earthquake scenarios and relevant literature, the main influential criteria and distance classes were determined. These criteria and distance classes were then weighted and integrated using the Analytic Hierarchy Process (AHP) and Geographic Information System (GIS) methods to generate an optimal location map.ResultsImplementation of the proposed method in Tehran resulted in an optimal location map for FFE-specific emergency water reservoirs. Results indicated that locating reservoirs within 4,000 m of major routes, fire stations, and commercial, industrial, and therapeutic centers simultaneously ensures fire engine access within 10 mins even under worst-case conditions.DiscussionFurthermore, optimally siting reservoirs within 800 m of demand points reduces access time to below 2 mins.